Energy efficient laser beam welding of metals with a ultra-high brightness direct-diode laser system - Laukart, Artur; Dobler, Michael; Kohl, Stefanie; Fritsche, Haro; Grohe, Andreas; Kruschke, Bastian; Schmidt, Michael (Energy Efficiency in Strategy of Sustainable Production, 2015)
The rising level of automation in the automotive industry also involves the use of more and more machines and with that an increase in power consumption. This requires the employment of more efficient production processes with higher efficiency. Laser beam welding offers the opportunity to substitute conventional laser sources like solid state lasers with ultra-high brightness direct-diode laser systems which have the advantage of less power consumption at a comparable beam quality. However, the absorption of laser radiation on metallic surfaces depends on the wavelength, thus the effect of the direct-diode laser wavelength on the welding process has to be investigated. In our research the effect of the laser wavelength on energy efficiency was studied by means of numerical simulations. Furthermore, experimental investigations were carried out to validate the numerical solutions. Different aluminum alloys and steel materials which are used in the automotive environment were investigated within the experiments. Due to the current lack of direct-diode laser systems with a laser power comparable to conventional laser systems, numerical simulations were also used to analyze these future systems. Thus we were able to assess the increase of efficiency in laser beam welding which will be achievable with future high-power direct-diode laser systems.
Keywords: laser beam welding; ultra-high brightness direct diode laser; high beam quality; numerical simulation; process modeling; automotive; energy efficiency

Experimental and Numerical Investigations of Laser Beam Welding with an Ultra-high Brightness Direct-diode Laser - Laukart, Artur; Kohl, Stefanie; Fritsche, Haro; Grohe, Andreas; Kruschke, Bastian; Schmidt, Michael (Physics Procedia, 2016)
Laser beam welding of steel sheets with conventional disc and fibre lasers is part of many manufacturing processes, e.g. car manufacturing. In modern times, all manufacturing processes are also evaluated regarding sustainability. Although conventional beam sources have an ever increasing efficiency, direct-diode lasers are said to make a step in the wall-plug efficiency in comparison to conventional beam sources due to a missing brightness-converter. Investigations concerning laser beam welding with ultra-high brightness direct-diode lasers were carried out, showing heat conduction welding as well as deep penetration welding of 22MnB5 steel sheets is possible. Furthermore a beam parameter product of about 8 mm-mrad was measured, showing comparable beam quality to conventional disc and fibre lasers. Metallographic cuts were used for determining the welding penetration depth and cross-section. Especially the cross-sections, as a measure for process efficiency, show almost the same result using a direct-diode laser or a disc laser. Due to the limited laser power of 500W, numerical simulations were used to extend the experimental result
Keywords: Laser beam welding; direct-diode laser; process modeling; process efficiency

Geometry dependent microstructures: bug or feature? - Hagen, Jan Frederik; Rasch, Michael; Kohl, Stefanie; Schmidt, Michael (Procedia CIRP, 2018)
Selective laser melting (SLM) promises not only geometric freedom, but is envisioned to allow tailored microstructures as well. While the possibility to be able to build chosen microstructures in certain areas of a part is often seen as a feature, the local change in microstructure due to a changing geometry is just as often seen as a bug. Since the formation of microstructure depends on local temperature gradient and solidification rate, simulations must be able to predict both quantities to reflect experimental results. We use thermomechanical simulations on the part scale and thermofluidic simulations on the powder scale to show the influence of geometry on the temperature gradient and solidification rate. Being able to predict these quantities the user can actively decide between feature and bug and adjust process parameters accordingly.
Created from Fastlane, Scopus look-up
Keywords: Cooling rates; Microstructure; Selective laser melting; Simulation

Improving weld quality and welding distortion in laser beam welding of dissimilar high strength steels - Hugger, Florian; Mann, Vincent; Kohl, Stefanie (Beam technologies & laser application, 2016)

Influence of powder distribution on process stability in laser beam melting: Analysis of melt pool dynamics by numerical simulations - Gürtler, Franz-Josef; Karg, Michael; Dobler, Michael; Kohl, Stefanie; Tzivilsky, Ilya; Schmidt, Michael (Proceedings of the 25th Annual International Solid Freeform Symposium, 2014)
The occurrence of defects in the additive manufacturing process of laser beam melting in metal powder bed can be reduced through empiric parameter optimization – but knowledge about basic effects like the influence of the composition of the powder layer on the melt pool is still limited. Particle size distribution and powder layer inhomogeneity after layer coating influence melt pool dynamics and may cause defects in the work pieces. This correlation can hardly be analyzed in experiments, so a three-dimensional transient numerical simulation model is used. The model is based on the continuity equation, the heat equation and the Navier-Stokes equation. Therefore, the finite-volume method capabilities in OpenFOAM are used. The free surfaces of the multi-phase system are calculated using the volume of fluid method. The powder beds have unimodal or bimodal distributions without random effects in the particle composition. Their density and thermal conductivity is adapted to reality. The investigations of the melt pool and the porosity formation demonstrate an advantage of more and smaller particles in the powder for compensation of defects in the powder bed, similar to the results of the experiment
Keywords: Additive Fertigung; Laserstrahlschmelzen im Pulverbett; Lasermaterialbearbeitung; Prozesssimulation

Microscale modelling for powderbed based laser melting: A testbed for new system technology - Hagen, Jan Frederik; Kohl, Stefanie; Schmidt, Michael (Simulation for Additive Manufacturing 2017, Sinam 2017, 2017)
CRIS-Team Scopus Importer:2022-06-05
Keywords: Beam shaping; Microscale simulation; Selective laser melting

Multi-physical modeling of laser material processing - process analysis and optimization - Schmidt, Michael; Dobler, Michael; Kohl, Stefanie; Gürtler, Franz-Josef; Leitz, Karl-Heinz; Otto, Andreas (International Laser Symposium Fiber & Disc (FiSC 2012), 2012)

Numerical Analysis of the Influence of Beam Characteristics onto the Process Dynamics during Laser Cutting - Kohl, Stefanie; Schmidt, Michael (The 32nd International Congress on Applications of Lasers & Electro-Optics (ICALEO®) 2013, 2013)
Laser cutting currently represents the most common laser-based process in production technology. With the ongoing development of remote laser cutting technologies, such as remote fusion cutting and remote ablation cutting, its field of application will widen even more. Exploring these processes, simulations offer major advantages compared to experiments. Not only do they offer insight into process variables that are not or only hardly accessible experimentally, but they also allow us to investigate cutting with process parameters that are not even experimentally available yet, e.g. alternative beam sources. Therefore, we refined our transient, numerical simulation model for laser-material processing and applied it on laser cutting. In contrast to other simulation models which focus on certain aspects, our model has a comprehensive objective, which enables us to examine various laser-material processing techniques with the same universal model. After introducing the model, we present results on the process dynamics of Remote Fusion Cutting and Remote Ablation Cutting. For comparison, we show current results on gas-assisted fusion cutting and demonstrate that our results agree well with experiments. Conclusively, we present how laser characteristics, such as polarization and beam profile, influence the process dynamics, which will become increasingly important with the development of new beam sources.
Keywords: Lasermaterialbearbeitung; Laserstrahlschmelzschneiden; Prozesssimulation

On Plasma Formation in CO2 Fusion Laser Cutting of Stainless Steel - Sichani, E. Fallahi; Kohl, Stefanie; Schmidt, Michael; Kruth, J. -P.; Duflou, J. R. (Physics Procedia, 2012)
This paper discusses the mechanisms for emergence of laser-induced plasma (LIP) in fusion CO2 laser cutting of stainless steel plates. Experimental observations and simulation results are presented to explain why cutting at high velocity increases the risk of LIP formation despite the depleted energy input per unit length.
Created from Fastlane, Scopus look-up
Keywords: absorption coefficient; CO; laser-induced plasma; real-time monitoring

Scaling melt pool geometry over a wide range of laser scanning speeds during laser-based Powder Bed Fusion - Döring, Markus; Boussinot, Guillaume; Hagen, Jan Frederik; Apel, Markus; Kohl, Stefanie; Schmidt, Michael (Procedia CIRP, 2020)
Generating dense parts from laser-based Powder Bed Fusion of metals often requires the adaption of laser scanning speed. Thereby, scanning speed is lost as a degree of freedom for tailoring the microstructure. This paper addresses this issue by using an analytical model from literature to achieve equal melt pool width and depth for a range of factor 12 for laser scanning speeds and by examining the resulting specimen densities for this range of scanning speeds. The melt pool width and the melt pool depth of a dense reference specimen are measured. The measured melt pool width and melt pool depth are defined as the target sizes of the melt pool for all examined scanning speeds, as this is expected to result in dense specimens from a geometrical point of view. The target size shall be achieved by using an analytical model from the literature. This strategy is chosen to estimate the necessary energy input for creating dense specimens while avoiding incomplete fusion and keyholing. Defects mechanisms like splatters and cracks are excluded from this initial examination.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Line energy; Melt pool depth; Melt pool geometry; Normalized enthalpy; PBF; Volume energy density

Shaped laser beam profiles for heat conduction welding of aluminium-copper alloys - Rasch, Michael; Roider, Clemens; Kohl, Stefanie; Strauß, Johannes; Maurer, Niklas; Nagulin, Konstantin Yu.; Schmidt, Michael (Optics and Lasers in Engineering, 2019)
Heat conduction welding is often used where weld seams with a high surface quality and the exact retention of the chemical composition are needed. This study investigates the influence of intensity profiles in laser beam welding with laser powers up to 3.2 kW. The resulting process windows for heat conduction mode welding, the melt pool shape, the process stability and the dynamics, and the produced surface roughness are analysed. Therefore, three different intensity profiles are created with diffractive optical elements and the process dynamics are monitored with two high-speed cameras. Before analysing etched cross sections with respect to microstructural properties, the surface roughness is measured on all produced samples with a laser scanning microscope. With beam shaping, we found that a high peak intensity does not necessarily lead to an instable melt pool and that the distribution itself plays the major role. The use of shaped beam profiles leads to a more stable process and an enlarged heat conduction process regime compared to a defocussed multimode spot of the same size. Applying shaped laser beam profiles surface roughness close to laser polished surfaces can be achieved while also simultaneously enlarging the weld cross section area.<br
Keywords: Heat conduction mode laser beam welding; Surface roughness; Beam shaping; Diffractive optical elements; Aluminium alloys; Numerical process simulation

Spatter formation in laser beam welding using laser beam oscillation - Hugger, Florian; Hofmann, Konstantin; Kohl, Stefanie; Dobler, Michael; Schmidt, Michael (Welding in the World, 2015)
This paper presents an approach towards a better understanding of spatter formation in laser beam welding. Hereunto, experimental investigations and numerical simulation are carried out. For the study, various steels and aluminium alloys were selected to investigate the influences of alloying elements upon spatter formation. The welding was performed by applying a laser beam oscillation technique in which weld seam is generated by a spiral movement of the laser beam, in order to check the influence of weld pool movement according to spatter formation. This strategy was also transferred to the numerical simulation to get a detailed insight into the processes taking place in the keyhole when spatters form. Furthermore, a new detection method is presented which allows a three-dimensional tracking of spatters by using a pair of synchronised stereo cameras.
Created from Fastlane, Scopus look-up
Keywords: Imaging; Laser beams; Laser welding; Simulating; Spatter

State-of-the art data normalization methods improve NMR-based metabolomic analysis - Kohl, Stefanie M.; Klein, Matthias S.; Hochrein, Jochen; Oefner, Peter J.; Spang, Rainer; Gronwald, Wolfram (Metabolomics, 2012)
Extracting biomedical information from large metabolomic datasets by multivariate data analysis is of considerable complexity. Common challenges include among others screening for differentially produced metabolites, estimation of fold changes, and sample classification. Prior to these analysis steps, it is important to minimize contributions from unwanted biases and experimental variance. This is the goal of data preprocessing. In this work, different data normalization methods were compared systematically employing two different datasets generated by means of nuclear magnetic resonance (NMR) spectroscopy. To this end, two different types of normalization methods were used, one aiming to remove unwanted sample-to-sample variation while the other adjusts the variance of the different metabolites by variable scaling and variance stabilization methods. The impact of all methods tested on sample classification was evaluated on urinary NMR fingerprints obtained from healthy volunteers and patients suffering from autosomal polycystic kidney disease (ADPKD). Performance in terms of screening for differentially produced metabolites was investigated on a dataset following a Latin-square design, where varied amounts of 8 different metabolites were spiked into a human urine matrix while keeping the total spike-in amount constant. In addition, specific tests were conducted to systematically investigate the influence of the different preprocessing methods on the structure of the analyzed data. In conclusion, preprocessing methods originally developed for DNA microarray analysis, in particular, Quantile and Cubic-Spline Normalization, performed best in reducing bias, accurately detecting fold changes, and classifying samples. © 2011 The Author(s).
Created from Fastlane, Scopus look-up
Keywords: Classification; Data normalization; Metabolomics; NMR; Preprocessing

Towards numerical determination of distortion in laser welding - Kohl, Stefanie; Hugger, Florian; Mann, Vincent; Schmidt, Michael (Thermal Forming and Welding Distortion: Proceedings of the IWOTE`14:International Workshop on Thermal Forming and Welding Distortion, 2014)
During the development of new products, the influence of production technologies on the properties of the components have to be taken into account. Examples for undesired effects on the assembly geometry are back-bending or welding distortions, which can significantly change the dimensions of a part during the production process. Especially in welding, the welding distortion is strongly dependent on the chosen parameters, as these have a significant influence on the shape of the weld seam and hence the distortion. However, the resulting deformation has to be known in the design phase before production starts. Consequently, cost-expensive and time-consuming experimental investigations are necessary for optimization of the process parameters. For reduction of the experimental effort, numerical simulations have the potential to predict the resulting properties of the assembly and therefore, they offer the opportunity of making the development of production processes more time and cost-efficient. Nevertheless, currently there is no model available that enables virtual development of a product with intrinsic process parameter optimization. In this paper, we present experimental results of the influence of welding parameters upon welding distortion in fillet weld configuration. The investigated parameters are energy input per unit length, focus position, beam displacement and angle of incidence. We measured the distortion of the high strength steel welds time-resolved via several tactile sensors while we determined the weld seam shape by cross-section analysis and high-speed imaging. The investigated geometrical factors are compared to those of numerical process simulations. In the simulations we used a transient fluid dynamical finite volume model published previously. The model takes into account heat input by angle and polarization dependent absorption as well as multiple reflections inside the keyhole. Also, the model includes phase changes and their enthalpies, conductive and convective heat transfer and a keyhole surface calculated self-consistently from surface tension, flow pressure and evaporation pressure. We evaluate and compare the results of the simulation model regarding weld seam geometry and distortion to the experimental work in order to reach a numerical simulation model for welding distortion which will facilitate completely virtual product design without the need of prior experimental investigations.
Keywords: Laserstrahlschweißen; Lasermaterialbearbeitung; Prozesssimulation

Transient numerical simulation of CO2 laser fusion cutting of metal sheets: Simulation model and process dynamics - Kohl, Stefanie; Leitz, Karl-Heinz; Schmidt, Michael (Proceedings of the 37th International MATADOR Conference, 2013)
Simulations are a versatile tool of increasing importance for profound analysis and comprehensive understanding of laser-based material processing. Based on our simulation model of laser-matter interaction, we developed a numerical three-dimensional model for the transient simulation of fusion cutting of sheet metal. This model is based on the finite-volume method (FVM) and covers various laser-metal interaction mechanisms, such as multiple surface reflection and absorption according to Fresnel, but also more complex interactions like absorption in the metal plasma. In this study, we focused on a Gaussian shaped CO2 laser beam applied for the cutting and steel sheets. The implemented physics include fluid and vapor dynamics according to Navier-Stokes, heat conduction, the surface tension of the liquid-vapor interface and the modeling of the enthalpies of fusion and vaporization. As accurate input parameters are crucial for any simulation, special focus was put on the implementation of material properties at temperatures around the melting point. The additional modeling of inert process gas ensures realistic blow-out of the molten material. Furthermore, adaptive meshing enables high calculation accuracy in the areas of interest while minimizing computation time drasticall
Keywords: Simulation; Lasermaterialbearbeitung; Laserstrahlschmelzschneiden; Prozesssimulation

Why Color Matters—Proposing a Quantitative Stability Criterion for Laser Beam Processing of Metals Based on Their Fundamental Optical Properties - Kohl, Stefanie; Kaufmann, Florian; Schmidt, Michael (Metals, 2022)
With its excellent automation capability and localized energy input enabling precise, reproducible welds, laser beam welding represents a preferred industrial joining technology. Electro-mobility drastically increases the need for defect-free and automatable copper joining technologies. However, copper welds that are produced with state-of-the-art infrared lasers often suffer from spattering and porosity. Recent publications show distinct improvements using novel beam sources at visible wavelengths, attributing them to increased absorptivity. Nevertheless, this cannot fully explain the steadier process behavior. This wavelength-dependent process stability has not yet been investigated sufficiently. Therefore, we have developed a predictive material-dependent criterion indicating process stability based on the example of copper heat-conduction spot welding. For this purpose, we combined energy balances with thermo-physical material properties, taking into account the wavelength and temperature dependence of the optical properties. This paper presents the key mechanism that we identified as decisive for process stability. The criterion revealed that X-points (unique, material-specific wavelengths) represent critical stability indicators. Our calculations agree very well with experimental results on copper, steel and aluminum using two different wavelengths and demonstrate the decisive, material-dependent wavelength impact on process stability. This knowledge will help guide manufacturers and users to choose and develop beam sources that are tailored to the material being processed.<br
Keywords: laser beam welding; copper welding; wavelength dependence; optical properties; analytical modeling